Impact of activator type on the immobilisation of lead in fly ash-based geopolymer - Lee, S.; Van Riessen, Arie; Chon, C.; Kang, N.; Jou, H.; Kim, Y. (2016)
Immobilisation of heavy metals in geopolymers has attracted attention as a potential means of treating toxic wastes. Lead is known to be effectively immobilised in a geopolymer matrix, but detailed explanation for the mechanisms involved and the specific chemical form of lead are not fully understood. To reveal the effect of the activator types on the immobilisation of lead in geopolymers, 0.5 and 1.0 wt% lead in the form of lead nitrate was mixed with fly ash and alkaline activators. Different alkaline activators (either combined sodium hydroxide and sodium silicate or sodium aluminate) were used to achieve the target Si:Al ratios 2.0 and 5.0 in geopolymers. Zeolite was formed in aluminate-activated geopolymers having a Si:Al ratio of 2.0, but the zeolite crystallization was suppressed as lead content increased. No specific crystalline phase of lead was detected by X-ray diffraction, electron diffraction or FT-IR spectrometry. In fact, double Cs corrected TEM analysis revealed that lead was evenly distributed with no evidence of formation of a specific lead compound. A sequential extraction procedure for fractionation of lead showed that lead did not exist as an exchangeable ion in geopolymers, regardless of activator type used. Aluminate activation is shown to be superior in the immobilisation of lead because about 99% of extracted lead existed in the oxidizing and residual fractions.